2019
DOI: 10.1021/acs.jcim.9b00884
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening Approach for the Identification of Hydroxamic Acids as Novel Human Ecto-5′-Nucleotidase Inhibitors

Abstract: Ecto-5′-nucleotidase (ecto-5′-NT, CD73) is a zinc-binding metallophosphatase that plays a key role in extracellular purinergic pathways, being implicated in several physiological and pathophysiological processes, such as immune homeostasis, inflammation, and tumor progression. As such, it has been recognized as a promising biological target for many diseases, including cancer, infections, and autoimmune diseases. Despite its importance, so far only a few inhibitors of this target enzyme are known, most of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…Thus, the location of hydrogen bonds is essential to achieve potent ligand binding and the effect of protein environment on this type of interaction should be carefully considered during visual analysis. In addition to formed hydrogen bonds, all unsatisfied hydrogen bond donor and acceptor groups without interacting counterparts, in particular those buried in the binding site, need to be evaluated, as they generally result in reduced binding free energies due to an uncompensated desolvation free energy penalty. , In metalloproteins, distinct electrostatic interactions with metal cofactors can be of major importance for ligand potency (Figure A). ,, Interestingly, none of the studies reviewed in this perspective reported the consideration of weak hydrogen bonds, halogen bonds, orthogonal dipole interactions, or amide−π interactions as a criterion during visual inspection (see also survey results for additional details).…”
Section: Criteria During Visual Inspectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the location of hydrogen bonds is essential to achieve potent ligand binding and the effect of protein environment on this type of interaction should be carefully considered during visual analysis. In addition to formed hydrogen bonds, all unsatisfied hydrogen bond donor and acceptor groups without interacting counterparts, in particular those buried in the binding site, need to be evaluated, as they generally result in reduced binding free energies due to an uncompensated desolvation free energy penalty. , In metalloproteins, distinct electrostatic interactions with metal cofactors can be of major importance for ligand potency (Figure A). ,, Interestingly, none of the studies reviewed in this perspective reported the consideration of weak hydrogen bonds, halogen bonds, orthogonal dipole interactions, or amide−π interactions as a criterion during visual inspection (see also survey results for additional details).…”
Section: Criteria During Visual Inspectionmentioning
confidence: 99%
“…While the displacement of water molecules is favorable due to an increase in entropy and sometimes enthalpy, some may form enthalpically strong interactions with the protein and bridge ligand–protein interactions favorably contributing to the binding free energy. Thus, solvation effects such as water-mediated interactions should be considered in visual inspection (Figure B,C). , However, the proper assessment of the multifaceted water behavior is by far not trivial even for extremely advanced experts. Moreover, the solvation scenario in the binding site in the apo state (no ligand present) is not routinely included in the visual comparison.…”
Section: Criteria During Visual Inspectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, APCP became a prototype for drug development (Bhattarai et al, 2015;Corbelini et al, 2015;Bhattarai et al, 2020). In addition, the recent availability of the crystal structures of ecto-5′-nucleotidases has led to the development of numerous docking and virtual screening studies (Knapp et al, 2012;Bhattarai et al, 2019;Viviani et al, 2020).…”
Section: Ecto-59-nt (Cd73) Inhibitorsmentioning
confidence: 99%
“…This and another small molecule inhibitor (LY3475070) are currently being evaluated in phase one clinical trials. In addition to APCP based inhibitors of CD73, descriptions of numerous other inhibitors of the enzyme can be found in the literature (Figueiró et al, 2014;Baqi, 2015;Yang et al, 2017;Ghoteimi et al, 2019;Iqbal et al, 2020;Viviani et al, 2020). Finally, nucleoside analogues with two carboxylate groups and benzothiazine derivatives are CD73 inhibitors for treating cancer that have been patented (Gong et al, 2018;Ghoteimi et al, 2019).…”
Section: Ecto-59-nt (Cd73) Inhibitorsmentioning
confidence: 99%